User Experience Using Motion Capture: Simulation of Human Motion for Multimedia Applications - Joon, Jong Sze; Thwaites, Harold; Weng, Khong Chee (2008)
This paper presents a motion-capture-based control framework by simulating three core motions namely walking, jumping and running to enhance user experience for Multimedia applications. Using MWalker V1 application, a user can directly control the full body motion of an avatar in virtual environments with different physical attributes for various multimedia applications. However, there are still a few fundamental problems. This research outlines how different physique produces different behavioural patterns based upon mass and proportion. This research considers 'motion' to identify the differences in each subject's physical attributes by sampling subjects of physical differences. The purpose of the research is to study the detail of motion of various subjects with differences in physical attributes, for simulation of human motion for multimedia applications.